Athletic identity and self-esteem among active and retired Paralympic athletes - Marin-Urquiza, A.; Ferreira, J. P.; Van Biesen, D. (European Journal of Sport Science, 2018)
Athletic identity (AI) has been suggested as a variable that can have an impact on the psychological health of the athletes upon retirement. The aim of this study was to provide more insight on the transition out of elite sport by assessing and comparing the extent of AI and self-esteem in an active group (AG) and a retired group (RG) of Paralympic athletes. Perceived stress and depressive symptoms were additionally assessed in the AG and RG, respectively. A non-probability sampling method was used to recruit active and retired Paralympic athletes (AG, n = 43; RG, n = 41, where 35 retired voluntarily and 6 retired involuntarily) with visual or physical impairments, from Dutch-, English-, Portuguese- and Spanish-speaking countries. Participants completed an electronic survey with questionnaires to assess the study variables mentioned above. Descriptive analysis, comparisons (Mann-Whitney U test and t-test) and Spearman`s correlation coefficient were performed for the statistical analysis. Scores of AI were significantly lower in the RG (44.6 ± 9.6) compared to the AG (49.4 ± 8.9); t(82)= 2.36, p= .021, d 0.51. No differences in self-esteem were found between RG and AG; however, within the RG, athletes who involuntarily retired (21 ± 7.1) had significantly lower self-esteem scores than those who retired voluntarily (25.2 ± 4.2); t(39) = 2.04, p = .049, d = 0.73. In conclusion, free choice upon retirement can positively influence the athletes` self-esteem, whereas a strong AI may negatively influence the retirement process, as it was positively correlated with depressive symptoms (= .409, p = .008). These findings can have practical implications for sport psychologists to better support their athletes.